United States : 2009 Article IV Consultation; Staff Report; Staff Supplement; and Public Information Notice on the Executive Board Discussion. (IMF Staff Country Reports; Country Report ;, 2009)
This 2009 Article IV Consultation highlights that the U.S. economy has experienced the worst financial crisis since the Great Depression. In the second half of 2008, financial pressures intensified and came to a head with the failure of Lehman Brothers in September. Executive Directors have commended the authorities' forceful and internationally coordinated actions to stabilize and repair the financial sector. As a result of their increasingly strong and comprehensive policy measures, the sharp fall in economic output seems to be ending, and confidence in financial stability has strengthened.